Looking at randomized trials with the critical eyes of epidemiologists: the case of screening colonoscopy - Brenner, Hermann; Heisser, Thomas; Hoffmeister, Michael (European journal of epidemiology, 2025)
Based on compelling evidence from observational epidemiological studies, screening colonoscopy has since long been thought to strongly lower the burden of colorectal cancer (CRC), both by early detection of prevalent CRC and prevention of incident CRC through detection and removal of precancerous lesions. Widespread offer and use of screening colonoscopy went along with a dramatic decline in CRC incidence in screening age groups in the US, in contrast to an increase in incidence at younger ages and in countries not engaging in CRC screening. The recently published 10-year results from the NordICC trial, the first randomized clinical trial (RCT) reporting long-term effects of screening colonoscopy on CRC risk and mortality, has been widely interpreted as challenging the evidence for strong efficacy of screening colonoscopy. Such reasoning was based on the trust that randomization in this large-sized trial should have prevented any residual confounding that might have affected the observational epidemiological studies. However, randomization cannot prevent other potential biases which should be carefully addressed and minimized in both observational and interventional studies. We illustrate that such biases may have led to major underestimation of screening effects in the NordICC trial. The observed patterns underline the need for more rigorous efforts to prevent and correct for such biases, along with the need to derive more informative metrics of screening efficacy. Such metrics should include informative estimates of screening colonoscopy effects on both early detection of prevalent CRC cases and prevention of incident CRC cases. The momentum for CRC screening should by no means slowed by misinterpretation of the NordICC trial evidence.